Hashish Body Packing: A Case Report - Manuel Jesus Soriano-Perez; Jose Luis Serrano-Carrillo; Inmaculada Marin-Montin; Alfonso Cruz-Caballero (Case Reports in Medicine)
A 42-year-old African male was brought by the police to the emergency department under suspicion of drug smuggling by body-packing. Plain abdominal radiograph showed multiple foreign bodies within the gastrointestinal tract. Contrast-enhanced abdominal CT confirmed the findings, and the patient admitted to have swallowed “balls” of hashish. Body-packing is a recognized method of smuggling drugs across international borders. Body packers may present to the emergency department because of drug toxicity, intestinal obstruction, or more commonly, requested by law-enforcement officers for medical confirmation or exclusion of suspected body packing.